2014
DOI: 10.1002/0471140856.tx2307s61
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Drug‐Induced Bile Salt Export Pump (BSEP) Interference

Abstract: Numerous drugs have been shown to inhibit the activity of the Bile Salt Export Pump (BSEP in humans, Bsep in animals), and this is now considered to be one of several mechanisms by which idiosyncratic drug-induced liver injury (DILI) may be initiated in susceptible patients. The potential importance of BSEP inhibition by drugs has been recognized by the European Medicines Agency and the International Transporter Consortium, who have recommended that it should be evaluated during drug development when evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Early detection of DILI (particularly, cholestasis) remains a challenge for pharmaceutical industries and regulatory agencies. According to the International Transporter Consortium and guidelines on the investigation of drug interactions from the European Medicines Agency (Zamek-Gliszczynski et al, 2012), inhibition of the bile salt export pump (BSEP), which plays a major role in BA canalicular transport (Jansen et al, 1999;Stieger, 2010), should be evaluated during drug development when evidence of cholestatic liver injury has been observed in nonclinical safety studies or in human clinical trials (Kenna, 2014). Indeed, many drugs reported to cause DILI have been identified as efflux transporter inhibitors (Morgan et al, 2010;Stieger, 2010;Dawson et al, 2012;Pedersen et al, 2013), but a significant number of false positives has been found (Pedersen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of DILI (particularly, cholestasis) remains a challenge for pharmaceutical industries and regulatory agencies. According to the International Transporter Consortium and guidelines on the investigation of drug interactions from the European Medicines Agency (Zamek-Gliszczynski et al, 2012), inhibition of the bile salt export pump (BSEP), which plays a major role in BA canalicular transport (Jansen et al, 1999;Stieger, 2010), should be evaluated during drug development when evidence of cholestatic liver injury has been observed in nonclinical safety studies or in human clinical trials (Kenna, 2014). Indeed, many drugs reported to cause DILI have been identified as efflux transporter inhibitors (Morgan et al, 2010;Stieger, 2010;Dawson et al, 2012;Pedersen et al, 2013), but a significant number of false positives has been found (Pedersen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma bile acid monitoring in animals has been proposed to provide a useful indirect biomarker of in vivo BSEP function (also see section “Data Interpretation: In Vitro/In Vivo Extrapolation, Quantitative Simulations”). However, increased plasma bile acid concentrations may also arise due to extrahepatic biliary obstruction, or as a secondary consequence of hepatocellular liver damage .…”
Section: Data Interpretation: In Vitro/in Vivo Extrapolation Quantitmentioning
confidence: 99%
“…6, 8, and 17). In addition, inhibition of the activity of the biliary efflux transporter BSEP plays a direct role in the mechanism by which numerous drugs can initiate DILI, while upregulation of the activity of other biliary efflux transporters plays an important hepatoprotective role in response to BSEP inhibition by drugs [11] (see also Chap. 15).…”
Section: Hepatobiliary Imaging Modalities and Tracersmentioning
confidence: 99%
“…A limitation of gadoxetate DCE-MRI is that, since gadoxetate is not transported by BSEP, it does not enable direct investigation of drug-induced inhibition of BSEP activity, which is considered to play an important role in DILI caused by many drugs [11]. Other probe substrates that are transported by BSEP, and ideally are BSEP-specific, are needed.…”
Section: Future Opportunities and Challengesmentioning
confidence: 99%